Analysis and prediction of subarachnoid hemorrhage burden in global, China, and Japan - Peng-Fei Ding; Chen-Jie Xing; Yong-Yue Gao; Chun-Hua Hang; Zong Zhuang; Wei Li (BMC Public Health)
Abstract Background Subarachnoid hemorrhage (SAH) remains a serious public health problem worldwide, especially in economically developed regions/countries. This study intends to thoroughly analyze the incidence, mortality, and disability-adjusted life years (DALYs) rate of SAH at the global, regional, and national levels. This study focused on the differences in SAH incidence between China and Japan from 1990 to 2019, and projected global, Chinese, and Japanese SAH incidence rates until 2030. Methods Data on the disease burden owing to SAH from 1990 to 2019 were obtained from the Global Burden of Disease (GBD) Study 2019. linear regression analysis was used to calculate the estimated annual percentage change (EAPC) and linear regression method was used to calculate the average annual percentage change (AAPC). Bayesian age-period-cohort (BAPC) model was used to predict the disease burden from 2020 to 2030. Results Globally, age-standardised incidence, mortality, and DALYs rates was declined from 1990 to 2019. In 1990–2019, the incidence of SAH decreased in China, while it increased in Japan, especially among middle-aged and elderly women. Projections suggest that the global incidence of SAH will decrease by 2.06% in 2030, with an increase of 6.24% in China and 13.82% in Japan, with the highest increase among Japanese women being 16.19%. Conclusions Global SAH incidence, mortality, and DALYs rates declined over the 1990–2019 period, with regional/national SAH mortality and DALYs rates negatively correlated with socio-demographic index (SDI), while SAH incidence was positively correlated with SDI. The incidence of SAH decreased in China and increased in Japan during this period. The predictions show that over the next 10 years, while the incidence of SAH continues to decline globally, the incidence of SAH in China and Japan has increased. Thus, SAH remains a serious disease burden that requires early intervention targeting risk factors and populations at risk that may have increased because of economic development.